The Effect Flavonoids Phaleria macrocarpa Fruit Extract on Thickness of Trabeculae, Cortex Ratio Femoral Bone and Aortic Intima-Media in Mice Menopause Model - Fadilah, R. A. Rahmawati Nurul; Khoirinda, Ani; Sutrisno, Sutrisno; Irwanto, Yahya; Anita, Kenty Wantri; Dewi, R. A. Rose Khasana (JURNAL INFO KESEHATAN, 2024)
A deficiency of the hormone estrogen at menopause can lead to an increased rate of the destruction of the bone tissue that leads to bone loss, which can lead to osteoporosis and impaired fat metabolism, which increases the risk of atherosclerosis. Phytoestrogens from flavonoid extract P. Macrocarpa, having effects similar to endogenous estrogens themselves, prevent osteoporosis and atherosclerosis in menopausal women. The purpose of this research is to assess the influence of flavonoids from P. Macrocarpa fruit extract on trabeculae cortex thickness, ratio of femoral bone, and aortic IMT (A-IMT) in a menopausal mouse model. The study was conducted in a true experimental-posttest-only control group design. Using 32 mice; namely KN (normal mice with no treatment), KP (OVX with no treatment), P1(OVX and given flavonoid 3.75 mg/mice/day), P2 (OVX and given flavonoid 7.5 mg/mice/day), P3(OVX and given flavonoid 11.25 mg/mice/day), P4 (OVX and given flavonoid 15 mg/mice/day), the treatment given within 14 days. Then the thickness of the trabeculae, cortex, and intima-media aorta with Hematoxylin-Eosin (HE) staining. In the trabeculae, cortex thickness ratio obtained KN results meaningfully dissimilar to the KP group and the P3 and P4 groups were meaningfully dissimilar from the KP. The A-BMI in KP is meaningfully dissimilar to P1, P2, P3 and P4. The conclusion of the study is flavonoid fruit extract P. Macrocarpa can increase the thickness ratio of trabeculae, and cortex femoral bone of mice menopausal model in groups P3, P4 and can decrease A-IMT starting in groups P1 to P4.